2020
DOI: 10.1017/s1431927620000033
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 Knockdown Induces Mitochondrial Dysfunction and Affects Early Developmental Competence in Porcine Embryos

Abstract: Connexin 43 (CX43) is a component of gap junctions. The lack of functional CX43 induces oxidative stress, autophagy, and apoptosis in somatic cells. However, the role of CX43 in the early development of porcine embryos is still unknown. Thus, the aim of this study was to investigate the role of CX43, and its underlying molecular mechanisms, on the developmental competence of early porcine embryos. We performed CX43 knockdown by microinjecting dsRNA into parthenogenetically activated porcine parthenotes. The bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“… 20 In many different tissue types, the decrease in Cx43 and the increase in ROS formation induced cell death. 21 In this study, with increased Casp3 expression, we showed that increased oxidative stress due to VCD exposure decreased Cx43 expression important for survival in granulosa cells and increases apoptosis in cells. Thus, thanks to this study, the relationship of VCD toxicity to Cx43 oxidative stress and apoptosis in damaged ovary was evaluated for the first time.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“… 20 In many different tissue types, the decrease in Cx43 and the increase in ROS formation induced cell death. 21 In this study, with increased Casp3 expression, we showed that increased oxidative stress due to VCD exposure decreased Cx43 expression important for survival in granulosa cells and increases apoptosis in cells. Thus, thanks to this study, the relationship of VCD toxicity to Cx43 oxidative stress and apoptosis in damaged ovary was evaluated for the first time.…”
Section: Discussionmentioning
confidence: 52%
“…In the same study, the researchers reported that intercellular apoptotic signals were transmitted between each other through gap junctions; therefore, the gap junction protein expressions increased in apoptosis, but Cx43 regulated the survival of cells rather than the channel function through which death signals were transmitted 20. In many different tissue types, the decrease in Cx43 and the increase in ROS formation induced cell death 21. In this study, with increased Immunohistochemical staining of Casp3 in ovary tissue.…”
mentioning
confidence: 49%
See 2 more Smart Citations
“…Connexin-43 knockdown in parthenogenetically activated porcine embryos was responsible for the reduction of the membrane permeability, mitochondrial membrane potential and ATP production, and for the enhanced level of reactive oxygen species. Additionally, blastocyst developmental rate, and the total cell number were decreased [ 85 ]. The importance of Cx43 for the oocyte quality was also confirmed in bovine.…”
Section: Pannexin and Connexin Related Pathologies Which Impact Oocyte Developmental Competencementioning
confidence: 99%